Penerapan Kesehatan Dan Keselamatan Kerja Pada Pengangkutan Batubara Di PT Lematang Coal Lestari Muara Enim Sumatera Selatan - Nursani, Rodiyah; Yovanda, Ridho; Gumanti, Suhardiman (Universitas Pahlawan Tuanku Tambusai, 2024)
The occupational safety and health (K3) conditions of companies in Indonesia are estimated to be quite low, this can be seen from the high risk of accidents that can occur in a company. Work accidents occur due to workers, work tools and the work environment, so it is necessary to implement occupational safety and health (K3) in carrying out mining activities. Safety and health factors are very important because they have a big influence on employees, society and also company assets. The aim of this research is to look at the implementation of Occupational Health and Safety in coal transportation at PT Lematang Coal Lestari. The method used in this research was field observation in the form of visits and direct field observations as well as data collection in the form of interviews or surveys. The research results showed that from the 8 questionnaire questions given to 5 respondents, PT Lematang Coal Lestari (LCL) employees received very good responses. Keywords: Occupational Health and Safety, Transportation, Coal.